Hearing loss in patients with chronic kidney disease undergoing haemodialysis - Thimmappa T.D; Gangadhar K.S; Ramesh S; Manjula B (Al Ameen Medical College, 2024)
Background: Haemodialysis is a treatment for chronic renal failure/chronic kidney disease that significantly reduce the morbidity and postpone the mortality. However, studies have reported that in these patients, hearing loss symptoms were increasing and affecting their quality of life. Objectives: To determine the percentage, degree, and type of hearing loss in patients undergoing haemodialysis secondary to chronic renal failure and to determine the relationship between hearing loss and the number of haemodialysis procedures undergone (duration). Methods: This was a prospective study; data from patients with renal failure who were undergoing regular haemodialysis at our tertiary care centre hospital were collected. A routine otorhinolaryngological examination was performed, and hearing loss was determined using otoacoustic emission and pure tone audiometric studies. Statistical analysis was performed using Epi-Info software. Results: The prevalence of hearing loss among dialysis patients was 79.17%. It is a sensorineural type (SNHL) of deafness. The majority of cases had a mild type of hearing loss. No significant relationship was found between the number of haemodialysis and the degree of hearing loss in CRF patients in our study. Conclusions: SNHL is common in patients with chronic renal disorders on haemodialysis. Further study should be conducted with a larger population with follow-up.